2006
DOI: 10.1136/emj.2004.023291
|View full text |Cite
|
Sign up to set email alerts
|

Airway management in patients with a broadcomplex tachycardia requiring electrical cardioversion: a postal survey

Abstract: This study was to determine whether or not ED and ICU consultants would intubate an unstarved, haemodynamically unstable patient with a BCT requiring electrical cardioversion, and to determine the incidence of complications for both intubating and not intubating based on the responders personal experience. 174 postal questionnaires were sent to ED and ICU consultants in the Wessex and South West regions of England. They were asked whether or not they would intubate a patient that required electrical cardiovers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…This issue was investigated by means of a postal survey, when it was found that only a one-third of emergency physicians, and significantly only two-thirds of intensive care physicians (mainly anaesthetists) would adopt a tracheal intubation strategy in such scenarios. 18 In the authors' opinion both approaches should be considered acceptable and the anaesthetic technique tailored to individual patient circumstances. If the patient is obese, has recently ingested a large meal, has a history of oesophageal reflux and is relatively cardiovascularly stable then a RSI approach would seem prudent.…”
Section: Emergency Cardioversionmentioning
confidence: 99%
“…This issue was investigated by means of a postal survey, when it was found that only a one-third of emergency physicians, and significantly only two-thirds of intensive care physicians (mainly anaesthetists) would adopt a tracheal intubation strategy in such scenarios. 18 In the authors' opinion both approaches should be considered acceptable and the anaesthetic technique tailored to individual patient circumstances. If the patient is obese, has recently ingested a large meal, has a history of oesophageal reflux and is relatively cardiovascularly stable then a RSI approach would seem prudent.…”
Section: Emergency Cardioversionmentioning
confidence: 99%